2018
DOI: 10.1039/c8tx00093j
|View full text |Cite
|
Sign up to set email alerts
|

The neurotoxicity induced by PM2.5 might be strongly related to changes of the hippocampal tissue structure and neurotransmitter levels

Abstract: Objective: The complex components of PM2.5 including metal elements transported through the blood brain barrier could induce nervous system damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The neuronal damage in our PMB models were comparable to other in vitro models, [ 26 ] but more severe than in vivo chronic models. [ 27 ] First, we attributed the lower sensitivity toward PM2.5‐driven neuroinflammation to the heterogeneous populations of glial cells playing either proinflammatory or anti‐inflammatory roles depending on brain regions, [ 6 , 16 , 17 ] while our models could separate PM2.5‐involving proinflammatory immune cells from other populations. Second, inhaled particles can be removed by other immune cells in the respiratory system, such as alveolar macrophages and lung lymphatics, before reaching to the brain, [ 25 , 28 ] while our cellular models are a type of an acute model as we employed larger amounts of PM2.5 as described in the previous response.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal damage in our PMB models were comparable to other in vitro models, [ 26 ] but more severe than in vivo chronic models. [ 27 ] First, we attributed the lower sensitivity toward PM2.5‐driven neuroinflammation to the heterogeneous populations of glial cells playing either proinflammatory or anti‐inflammatory roles depending on brain regions, [ 6 , 16 , 17 ] while our models could separate PM2.5‐involving proinflammatory immune cells from other populations. Second, inhaled particles can be removed by other immune cells in the respiratory system, such as alveolar macrophages and lung lymphatics, before reaching to the brain, [ 25 , 28 ] while our cellular models are a type of an acute model as we employed larger amounts of PM2.5 as described in the previous response.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of mice exposed to PM 2.5 throughout gestation showed evidence of increased neuronal apoptosis, mitochondrial matrix swelling, and structural damage in the hippocampus of mouse pups following gestational exposure to PM. [66,97] Similarly to rodents exposed to PM postnatally, [59,97] gestationally-exposed offspring, tested at P30, demonstrated impaired spatial learning. [66] Increased ROS and NO production and decreased neurite outgrowth were observed in wild-type mouse hippocampal cultures treated with UFPM, altering NMDA receptor function and decreasing evoked post-synaptic currents of CA1 neurons.…”
Section: Mitochondrial Dysfunction Following Pm Exposurementioning
confidence: 99%
“…The main crustal elementsaluminium (Al), calcium (Ca), iron (Fe), magnesium (Mg) and potassium (K)and also toxic elements from anthropogenic sourceszinc (Zn), copper (Cu), lead (Pb), nickel (Ni), arsenic (As), cadmium (Cd) and antimony (Sb)have been detected in the atmospheric PM2.5 and PM1 (diameter ≤ 1.0 µm) samples in Asian megacities [4] and large European cities [5,6,7]. Interestingly, Pb is the most common metal in the air, while Fe, Zn, Cu and Pb are the most abundant metals in PM2.5 [8].…”
mentioning
confidence: 99%
“…Interestingly, Pb is the most common metal in the air, while Fe, Zn, Cu and Pb are the most abundant metals in PM2.5 [8]. Some studies have identified Pb as the third most common metal behind Fe and Zn [3,5,9] or as the second most common metal in others surveys [4]. While the limit for airborne Pb determined by the World Health Organization (WHO) is 0.5 µg/m 3 , it is regularly exceeded in many cities around the world.…”
mentioning
confidence: 99%